THE INFLUENCE OF PRICE, PROMOTION AND PRODUCT QUALITY ON SAMSUNG SMARTPHONE PURCHASE DECISIONS IN UMSU STUDENTS - Nadia Ika Purnama; Anggia Ramadhan; Ragil Kurniawan (Proceeding International Seminar of Islamic Studies, 2021)
The purpose of this study was to determine and analyze the effect of decisions on purchasing decisions, to analyze and to analyze the influence of promotion on purchasing decisions, to know and to analyze the influence of products on decisions made by decisions and to analyze the influence of the influence, promotion and product quality. partially or simultaneously on purchasing Samsung smartphones for Umsu students. The approach used in this research is an associative approach. The population in this study were all students while the sample that met the sampling criteria was carried out with 100 people using non-probability. The data analysis technique in this study used a questionnaire technique. The data analysis technique in this study used the Classical Assumption Test, Multiple Regression, Hypothesis Test (t test and F test), and the coefficient of determination. Data processing in this study used the SPSS (Statistic Package for the Social Sciens) software program version 22.00. The results of this study prove that partially the price has an effect on purchasing decisions, promotion has an effect on purchasing decisions. Product quality has an influence on purchasing decisions. Simultaneously Price, Promotion, and Product Quality influence Purchasing DecisionsKeywords: Purchase Decision, Price, Promotion, Product Quality